Perturbation with a constant drawdown of the underground water level in the perturbing well - M. M. Burakov (Известия высших учебных заведений: Геология и разведка, 2017)
On the basis of the method of integral relationships, an approximate solution of the problem of groundwater filtration in pressure aquifers has been obtained when they are tested with pumpings. The solution obtained is applicable for moments of time less than two orders than the approximate representation of the exact solution on which the existing technique for interpreting the results of the experimental filtration testing of horizons is based.